530 T-cell immunoglobulin– and mucin domain–containing (TIM)–3 downregulation in response to ex vivo activation and cancer targets correlates to NK cell functionality. (9th November 2020) - Dao, Tram; Matosevic, Sandro; Utturkar, Sagar; Lanman, Nadia
Abstract : Background: Natural killer (NK) cells are part of the innate immune system, but are capable of participating in both innate and adaptive immune responses due to their wide range of cytolytic activities, from degranulation, secretion of cytokines to antibody-dependent cell-mediated cytotoxicity. These are possible due to the cells' ability to recognize self and non-self-entities via the net signal generated from their activating and inhibitory receptors upon engagement. TIM-3 is a part of the NK receptor repertoire, expressed commonly on different lymphocytes. In T cells, TIM-3 is established as an inhibitory marker. However, in NK cells, the role of TIM-3 could be agonistic or antagonistic to NK cytotoxicity based on the disease type and activation status, though limited information is known about its role in cancer and its correlation to NK cell effector functions. Methods: We measured TIM-3 expression upon activation of human NK cells under various conditions. NK cells were isolated from peripheral blood of healthy donors and expanded either in K562-based feeder media or feeder-free OpTmizerTM media. After expansion, they were co-cultured for 4 hours with patient-derived glioblastoma multiforme cells (GBM43) at effector:target ratios of 2.5:1 and 10:1. To evaluate the effect of TIM-3 expression on NK cells, 7AAD/CFSE killing assays, CD107a degranulation and IFNγ secretion assays were carried out while blocking TIM-3 with neutralizing antibodies. Bioinformatics analysis of GBM patient RNAseq data was carried out to correlate TIM-3 expression with in vivo function, and this analysis is supplemented by phenotyping TIM-3 on NK cells isolated from patient samples in order to infer the role of this receptor in GBM. Results: We found that TIM-3 was downregulated on OpTmizerTM -cultured NK cells once exposed to cancer targets, and this correlated to a decreased in NK killing capacity when compared to feeder media-cultured NK cells, where the downregulation was not observed. Culturing NK cells in different derivatives of both media suggested that a combination of serum and cytokines can induce TIM-3 expression change to cancer targets. Flow cytometric assays revealed that while degranulation remained the same, the decreased in cytotoxicity corresponded to a decrease in IFNγ secretion. In GBM patient datasets, TIM-3 expression correlates to high IFN-γ levels and associates with both pro- and anti-tumorigenic functions. Here, we report a new role of TIM-3 in modulating NK functionality by correlating its loss to a loss in NK cell effector functions, and how its expression can be modified by ex vivo activation. Conclusions: TIM-3 expression on NK cells can be induced by ex vivo expansion, and this change in expression could influence NK cytotoxicity and cytokine secretion. Our data suggested that TIM-3 is not necessarily an inhibitory marker in GBM, and more likely to be a status marker or an activation limiter, working in conjunction with other receptors to modulate NK cell anti-tumor responses. Ethics Approval: This study was approved by Purdue Intuition's Ethics Board, approval number [1804020540].